The Influence of the Initial Angle of the Cut and the Depth of Cut on the Shaping Process to Edge Wear of HSS Chisel - Anrinal; Asmara Yanto; Hendriwan Fahmi; Yanto Darman (Jurnal Teknik Mesin, 2020)
The purpose of this research is to provide an overview of the effect of the initial angle of cut and depth of cut on the edge wear of the HSS chisel in the wear resistant steel cutting process using a scrap machine. This research was conducted using the KLOPP brand scrap machine, Type 550, Machine Code SC 01, Cutting speed (V) 15 m / min, Feeding motion (f) 0.4 mm / step, cutting time 5 minutes, using HSS Bohler scrap chisel Rapid Extra 1200 (3/8 "X 4") with variations in the initial angle of cutting (λ) 50 , 150, 250 and variations in the depth of cut (a) 0.4 mm, 0.8 mm and 1.2 mm. The results showed that an increase in the initial angle of cut and depth of cut tended to result in an increase in the edge wear of the HSS chisel.